2004
DOI: 10.4049/jimmunol.172.7.4575
|View full text |Cite
|
Sign up to set email alerts
|

Multiepitope Trojan Antigen Peptide Vaccines for the Induction of Antitumor CTL and Th Immune Responses

Abstract: We describe in this study a strategy to produce synthetic vaccines based on a single polypeptide capable of eliciting strong immune responses to a combination CTL and Th epitopes with the purpose of treating malignancies or preventing infectious diseases. This strategy is based on the capacity of Trojan Ags to deliver exogenous Ags into the intracellular compartments, where processing into MHC-binding peptides takes place. Our previous work demonstrated that Trojan Ags containing a CTL epitope localized to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 29 publications
3
76
0
Order By: Relevance
“…Both furin (11,12) and cathepsin S (14) have been involved in TAP-independent cross-priming of immunogens that originate from an exogenous source. However, as the cytosolic proteins Ova and cC-Ova did not induce CD8 ϩ T lymphocytes in TAP1-deficient mice, the evidence suggests that the potential of constructs like sC-Ova⌬C for in vivo immunization depends on direct priming by professional APC rather than on cross-priming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both furin (11,12) and cathepsin S (14) have been involved in TAP-independent cross-priming of immunogens that originate from an exogenous source. However, as the cytosolic proteins Ova and cC-Ova did not induce CD8 ϩ T lymphocytes in TAP1-deficient mice, the evidence suggests that the potential of constructs like sC-Ova⌬C for in vivo immunization depends on direct priming by professional APC rather than on cross-priming.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for TAP-independent pathways of Ag presentation by MHC class I molecules (4,5). The proteases involved include ER signal peptidase, trans-Golgi network furin and cathepsins for endogenously synthesized proteins (6 -10) and for internalized Ags (11)(12)(13)(14).…”
Section: Furin-processed Antigens Targeted To the Secretory Routementioning
confidence: 99%
See 1 more Smart Citation
“…Draining lymph node CD11c + DCs from mice cross presented OVA 48 h after injection of 3D8-OVA [250][251][252][253][254][255][256][257][258][259][260][261][262][263][264] . Ag targeting to the cross-presentation pathway in DCs has been studied using Ags coupled to carriers such as cell-penetrating peptides (CPPs) (27)(28)(29), endocytosed Hsps (9,30), and Abs against DC-specific endocytic receptors, including DC-SIGN and DEC205 (26). In particular, Ag targeting to the cross-presentation pathway in both murine and human DCs has been extensively studied by Steinman's group, using an anti-DEC205 Ab (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…33 When the HIV-I Tat peptide was linked to multiple CD8 and CD4 epitopes from OVA and furin-sensitive linker sequences were incorporated, potent CTL and Th responses were induced in vivo which showed striking prophylactic and therapeutic tumor protection against B16.OVA. 24 Previously, we have shown that immunizing mice with penetratin linked to the tumor-associated Mucin 1K b -restricted CTL peptide (MUC1-K b ), induced strong antigen-specific T-cell responses in vivo and tumor protection. 20 In the same study, mice immunized with penetratin linked to MUC1FP glutathione S-transferase fusion protein comprising of five variable number of tandem repeats from MUC1-induced antitumor responses in vivo.…”
Section: Penetratin Targets Antigen Presentation Pathways Ds Pouniotimentioning
confidence: 99%